Relationship between self-efficacy, engagement, and English academic achievement among junior- 2 students in Hebi Distribution, China - Zhang, Yue; Ahmad, Nor Aniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This study seeks to determine the relationship between self-efficacy, engagement, and academic achievement in English course among junior high school students in China. The respondents of this study consisted of 64 (34male, 30 female) junior-2 students studying in Hebi Distribute, Henan Province. The stratified random sampling technique was utilized in selecting a representative sample from the target population. The instruments used in this study included English Learners' Self-Efficacy Scale devised by Zhang Shufen (2006) and Students' Engagement Scale modified from Kong Qiping (2003). The results of this study revealed that junior-2 students had a medium level of English self-efficacy and engagement. Among the four sub-dimensions of students’ English self-efficacy, confidence and task sense sub-dimensions are at the high and low level respectively. All of the three sub-dimensions of student engagement (behavior engagement, cognitive engagement and emotional engagement) are at the middle level. Moreover, the strong positive significant interrelationship between students’ English self-efficacy and engagement has been clearly manifested. junior-2 students’ English self-efficacy and engagement are both positively intensively associated with English achievements. From the perspectives of each section of English self-efficacy, the Pearson correlation of task sense is highest, which implies that students’ perception of the task sense may have a more important effect on students’ achievement than other three sub-dimensions. Among students’ engagement, cognitive engagement has a more evident relation with English achievement than behavioral and emotional engagement. These results imply that junior-2 students who prefer cognitive engagement are seem to be conducive for gaining good English performance.